Sikap Kreatif Siswa Kelas X Jurusan Tata Busana Pada Mata Pelajaran Menghias Busana Di Sekolah Menengah Kejuruan Negeri 6 Padang - Wahyuni, Lisa; Ramainas, Ramainas; Adriani, Adriani (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This research is quantitative descriptive, which aims to describe the attitude of Creative Class X Subject Decorate Dress In dressmaking courses in Vocational School District 6, which includes the Padang curious, confident and independent, risk-taking, persevering and not easily bored. The population in this study were all students of class X subjects dressmaking SMK N 6 Padang, consisting of three classes totaling 88 people. This study uses total sampling technique that is the entire population sampled. The data collected in this study is primary data by means of questionnaires, the questionnaire contains questions relating to the creative attitude of students on subjects Decorate Dress linkert using scale models. Of the results showed that the attitude of the creative class X dressmaking courses on subjects Decorate Dress in SMK N 6 Padang is in the category of moderate (59.9%), with the indicators: 1. Curiosity is at the high category (63.4%), 2. Self-confidence and are in the category of moderate (57.4%), 3. Dare to take risks that are in the category of medium (57.0), 4. Persevering and not easily bored are at high category (61.9%). Keywords: Attitude Creative Students, Subjects Decorate Dress